On generalized ideal asymptotically statistical equivalent of order $α$ for functions - Öztürk, M.; Savaş, R. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We introduce new definitions related to the notions of asymptotically $\mathcal{I}_{λ}$ -statistical equivalent of order α to multiple L andstrongly $\mathcal{I}_{λ}$ -asymptotically equivalent of order $α$ to multiple $L$ by using two nonnegative real-valued Lebesque measurablefunctions in the interval $(1,∞ )$ instead of sequences. In addition, we also present some inclusion theorems.